A cross-sectional study of non-suicidal self-injury in adolescent depression: association with demographic characteristics and physiological indicators - He, Yangliuqing; Wei, Yuhan; Wang, Yiming; Liang, Fenrong; Ma, Tianpei (Frontiers in Psychiatry, 2024)
This study aims to explore the relationship between non-suicidal self-injury (NSSI) and demographic characteristics and physiological indicators among adolescents with depression. A cross-sectional study was conducted on 222 inpatients aged 13 to 18 with depression at the affiliated hospital of Guizhou Medical University. The results showed significant correlations between NSSI and factors such as gender, only-child status, age, ALT, TSH, FT4, and PLR. Among the study participants, the prevalence of NSSI was 40.5% and it was closely associated with female gender, non-only-child status, younger age, lower ALT, higher TSH, lower FT4, and higher PLR. However, there were no significant differences in TG, HDLC, LDLC, FT3, NLR, and MLR between the NSSI group and the non-NSSI group.